An anti-swelling hydrogel with excellent mechanical properties and its preparation method and application

By introducing materials such as chitosan and DMAEMA-MA into the hydrogel, a dual network structure is formed, which solves the problem of insufficient swelling resistance and conductivity of hydrogel underwater, and achieves the comprehensive effect of high strength, high toughness and conductivity, expands its potential for underwater application.

CN115651124BActive Publication Date: 2025-04-29JILIN INST OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211311049.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-04-29
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

Existing hydrogels cannot take into account excellent anti-swelling, high strength, high toughness and electrical conductivity, which limits their potential for underwater applications.

Method used

By introducing materials such as chitosan and DMAEMA-MA, an interpenetrating dual network structure is formed, and the anti-swelling and conductivity is improved by hydrogen bonding and electrostatic interaction, while improving mechanical properties through monomers such as acrylic.

Benefits of technology

It realizes the high swelling resistance, toughness and conductivity of the hydrogel in a water environment, and broadens its application in flexible wearable electronic devices and underwater sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115651124B_ABST
    Figure CN115651124B_ABST
Patent Text Reader

Abstract

A swelling-resistant hydrogel with excellent mechanical properties, and a preparation method and application thereof. The present invention belongs to the field of double-network hydrogels. The purpose of the present invention is to solve the technical problem that the existing hydrogels cannot take into account excellent swelling resistance, high strength and toughness, and electrical conductivity. The hydrogel of the present invention has an interpenetrating double network, wherein the chitosan molecular chain is used as the first network, butyl acrylate, 2-hydroxyethyl methacrylate and acrylic acid are used as monomers, and dimethylaminoethyl methacrylate maleate is used as a cross-linking agent to copolymerize to form a second network, and the first network and the second network form a double-network physical cross-linking structure with hydrogen bonding. The hydrogel prepared by the present invention has good mechanical properties, high continuous conductivity and swelling resistance. Based on these excellent properties, the hydrogel is expected to be used as a flexible wearable electronic device to broaden its application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of double network hydrogels, and specifically relates to an anti-swelling hydrogel with excellent mechanical properties and a preparation method and application thereof. Background Art

[0002] Hydrogel has become one of the candidate materials for wearable electronic devices and flexible strain sensors due to its own advantages such as stretchability, flexibility and elasticity. Although hydrogels have various properties such as mechanical properties, electrical conductivity and antifreeze. However, traditional hydrogels will inevitably swell in water environments. The swelling behavior will not only weaken the mechanical properties of the hydrogel, but also damage the performance of flexible energy storage devices and strain sensors due to the volume expansion of the hydrogel matrix.

[0003] In order to overcome the swelling problem of hydrogels, people have made many efforts, such as increasing the cross-linking density, introducing thermosensitive polymers into the network, blocking the interaction between polymers and water in the network, etc. However, this will bring the following problems: (i) hydrogels will become hard and brittle due to excessive cross-linking; (ii) the thermal response section needs to reach a critical temperature to exert anti-swelling behavior; (iii) intrinsic conductive hydrogels are usually mechanically brittle or have poor compatibility due to their strong hydrophobicity. Therefore, there is an urgent need to prepare anti-swelling, tough, and conductive polymers, which will broaden their potential underwater applications. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem that the existing hydrogel cannot have excellent anti-swelling, high strength and toughness and electrical conductivity, and to provide an anti-swelling hydrogel with excellent mechanical properties and a preparation method and application thereof.

[0005] One of the purposes of the present invention is to provide a method for preparing an anti-swelling hydrogel with excellent mechanical properties, the method being carried out according to the following steps:

[0006] Step 1: firstly mix acrylic acid (AA) and deionized water, then add chitosan (CS), heat and stir until completely dissolved, to obtain a mixed solution;

[0007] Step 2: Add 2-hydroxyethyl methacrylate (HEMA) and butyl acrylate (BA) to the mixed solution, mix well, add dimethylaminoethyl methacrylate maleate (DMAEMA-MA), ammonium persulfate aqueous solution (APS) and tetramethylethylenediamine (TEMED), and stir to obtain a hydrogel precursor;

[0008] Step 3: After degassing, the hydrogel precursor is injected into the mold, and then reacted at 60-70°C for 3-5 hours, and then frozen at -15 to -25°C for 10-14 hours, and thawed to room temperature to obtain an anti-swelling hydrogel with excellent mechanical properties.

[0009] It is further defined that the volume ratio of acrylic acid (AA) to deionized water in step 1 is (2-4):10.

[0010] It is further defined that in step 1, the mass ratio of chitosan (CS) to deionized water is 0.035-0.045.

[0011] It is further defined that the volume ratio of 2-hydroxyethyl methacrylate (HEMA) and butyl acrylate (BA) in step 2 to the deionized water in step 1 is (2-4):(0.5-0.7):10.

[0012] Further defined, in step 2, dimethylaminoethyl methacrylate maleate is prepared according to the following steps:

[0013] Add dimethylaminoethyl methacrylate (DMAEMA) to acetone, mix well and add maleate (MA), and react with stirring at 50°C for 4 hours under nitrogen protection. After the reaction is completed, cool at low temperature, filter under reduced pressure and dry in vacuum to obtain white needle-shaped crystals of dimethylaminoethyl methacrylate maleate.

[0014] It is further defined that the molar ratio of dimethylaminoethyl methacrylate (DMAEMA) to maleate (MA) is (1.8-2.2):1.

[0015] It is further defined that the mass ratio of dimethylaminoethyl methacrylate maleate in step 2 to the deionized water in step 1 is (0.01-0.05):1.

[0016] It is further defined that the volume ratio of the aqueous ammonium persulfate solution (APS) and tetramethylethylenediamine (TEMED) in step 2 to the deionized water in step 1 is (0.8-1.2):(0.08-0.12):10.

[0017] It is further defined that the concentration of the aqueous ammonium persulfate solution (APS) in step 2 is 35-45 mg / mL.

[0018] It is further defined that in step 3, the bubbles are removed by ultrasound, and the ultrasound time is 8-12 minutes.

[0019] It is further defined that the reaction in step 3 is carried out at 65° C. for 4 hours.

[0020] Further defined, in step 3, the mixture is frozen at -20°C for 12 hours.

[0021] The second object of the present invention is to provide an anti-swelling hydrogel with excellent mechanical properties prepared according to the above preparation method, which has an interpenetrating double network, wherein chitosan molecular chains serve as the first network, BA, HEMA and AA are used as monomers, and DMAEMA-MA is used as a crosslinking agent to copolymerize to form a second network, and the first network and the second network form a double network physical crosslinking structure with hydrogen bonding.

[0022] The third object of the present invention is to provide an application of the anti-swelling hydrogel with excellent mechanical properties prepared according to the above preparation method, which is used to prepare flexible wearable electronic devices.

[0023] Compared with the prior art, the present invention has the following significant effects:

[0024] The hydrogel prepared by the present invention has an interpenetrating double network, wherein the chitosan molecular chain is used as the first network, BA, HEMA and AA are used as monomers, and DMAEMA-MA is used as a crosslinking agent to copolymerize to form a second network, and the first network and the second network form a double network physical crosslinking structure with reversible hydrogen bond interaction, and the specific advantages are as follows:

[0025] 1) The method of the present invention not only improves the mechanical strength of the material by introducing chitosan, but also improves the anti-swelling property of the material by increasing the cross-linking density. At the same time, the introduction of acrylic acid not only promotes the dissolution of chitosan, but also further improves the mechanical properties by forming more hydrogen bonds with chitosan.

[0026] 2) In the method of the present invention, DMAEMA-MA not only acts as a crosslinker to prevent the diffusion of conductive ions in an aqueous environment, but also provides an ion migration channel for ion transport, thereby generating a huge conductivity. At the same time, on the basis of DMAEMA-MA, butyl acrylate (BA) further provides a diffusion barrier for the diffusion of conductive ions in an aqueous environment. In addition, the freeze-thaw treatment will impart gel structural stability by forming a more ordered network structure.

[0027] 3) The hydrogen bonds provided by the flexible PHEMA chains can resist the deformation of the hydrogel. The introduction of DMAEMA-MA significantly improves the mechanical properties, continuous electrical conductivity and anti-swelling properties of the hydrogel, broadening the application range of hydrogel materials.

[0028] 4) After the hydrogel prepared by the present invention is immersed in water, its mechanical properties are effectively improved due to hydrophobic aggregation. Due to these excellent properties, the hydrogel can be used as a signal acquisition module for flexible wireless sensors. The signal output by the hydrogel material is processed by a filtering circuit, an amplifying circuit and a digital processing unit. Then, it can be transmitted in the form of WiFi communication through a wireless module. The purpose is to stably and accurately detect human body movements in an underwater environment. The underwater anti-swelling strategy driven by the balance between the hydrophilic effect and the hydrophobic effect is expected to provide inspiration for the development of underwater sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the preparation process of DMAEMA-MA in the present invention;

[0030] Figure 2 The figure is a schematic diagram of the preparation process, formation mechanism and network structure of the hydrogel of the present invention;

[0031] Figure 3 ad are the mechanical properties display diagrams of the hydrogel prepared in Example 3;

[0032] Figure 4 It is a swelling curve diagram of the hydrogels prepared in Examples 2-3 and Comparative Example;

[0033] Figure 5 is a tensile stress-strain curve diagram of the hydrogel prepared in Examples 1-3;

[0034] Figure 6 This is a tensile stress-strain curve after underwater immersion obtained in Example 1;

[0035] Figure 7 This is a tensile stress-strain curve after underwater immersion obtained in Example 2;

[0036] Figure 8 This is the tensile stress-strain curve after underwater immersion obtained in Example 3. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0039] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0040] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0041] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0042] Example 1: Combination Figure 1-2 The preparation method of the anti-swelling hydrogel with excellent mechanical properties of this embodiment is carried out according to the following steps:

[0043] Step 1: First, mix 3 mL of AA and 10 mL of deionized water, then add 0.35 g of CS, heat and stir at 50 °C until completely dissolved to obtain a mixed solution;

[0044] Step 2:

[0045] First, 9.43 g (0.06 mol) of DMAEMA was added to 15 mL of acetone, and 3.48 g (0.03 mol) of maleate was added after mixing. Under nitrogen protection, the mixture was stirred at 50 ° C for 4 h. After the reaction was completed, it was cooled at low temperature, filtered under reduced pressure, and then vacuum dried at 65 ° C for 4 h to obtain white needle-shaped crystals of DMAEMA-MA.

[0046] Then, 3 mL of HEMA and 0.6 mL of BA were added to the mixed solution obtained in step 1, and after mixing, 0.1 g of DMAEMA-MA, 1 mL of ammonium persulfate aqueous solution (40 mg / mL) and 0.1 mL of TEMED were added, and the mixture was stirred to obtain a hydrogel precursor;

[0047] Step 3: The hydrogel precursor was ultrasonically degassed for 10 minutes and then injected into the mold, and then reacted at 65°C for 4 hours, followed by freezing at -20°C for 12 hours and thawing to room temperature to obtain an anti-swelling hydrogel with excellent mechanical properties.

[0048] Example 2: Combination Figure 1-2 The preparation method of the anti-swelling hydrogel with excellent mechanical properties of this embodiment is carried out according to the following steps:

[0049] Step 1: First, mix 3 mL of AA and 10 mL of deionized water, then add 0.35 g of CS, heat and stir at 50 °C until completely dissolved to obtain a mixed solution;

[0050] Step 2:

[0051] First, 9.43 g (0.06 mol) of DMAEMA was added to 15 mL of acetone, and 3.48 g (0.03 mol) of maleate was added after mixing. Under nitrogen protection, the mixture was stirred at 50 ° C for 4 h. After the reaction was completed, it was cooled at low temperature, filtered under reduced pressure, and then vacuum dried at 65 ° C for 4 h to obtain white needle-shaped crystals of DMAEMA-MA.

[0052] Then, 3 mL of HEMA and 0.6 mL of BA were added to the mixed solution obtained in step 1, 0.4 g of DMAEMA-MA, 1 mL of ammonium persulfate aqueous solution (40 mg / mL) and 0.1 mL of TEMED were added after mixing, and the hydrogel precursor was obtained after stirring;

[0053] Step 3: The hydrogel precursor was ultrasonically degassed for 10 minutes and then injected into the mold, and then reacted at 65°C for 4 hours, followed by freezing at -20°C for 12 hours and thawing to room temperature to obtain an anti-swelling hydrogel with excellent mechanical properties.

[0054] Example 3: Combination Figure 1-2 The preparation method of the anti-swelling hydrogel with excellent mechanical properties of this embodiment is carried out according to the following steps:

[0055] Step 1: First, mix 3 mL of AA and 10 mL of deionized water, then add 0.45 g of CS, heat and stir at 50 °C until completely dissolved to obtain a mixed solution;

[0056] Step 2:

[0057] First, 9.43 g (0.06 mol) of DMAEMA was added to 15 mL of acetone, and 3.48 g (0.03 mol) of maleate was added after mixing. Under nitrogen protection, the mixture was stirred at 50 ° C for 4 h. After the reaction was completed, it was cooled at low temperature, filtered under reduced pressure, and then vacuum dried at 65 ° C for 4 h to obtain white needle-shaped crystals of DMAEMA-MA.

[0058] Then, 3 mL of HEMA and 0.6 mL of BA were added to the mixed solution obtained in step 1, 0.4 g of DMAEMA-MA, 1 mL of ammonium persulfate aqueous solution (40 mg / mL) and 0.1 mL of TEMED were added after mixing, and the hydrogel precursor was obtained after stirring;

[0059] Step 3: The hydrogel precursor was ultrasonically degassed for 10 minutes and then injected into the mold, and then reacted at 65°C for 4 hours, followed by freezing at -20°C for 12 hours and thawing to room temperature to obtain an anti-swelling hydrogel with excellent mechanical properties.

[0060] Comparative Example: A method for preparing a hydrogel is carried out according to the following steps:

[0061] Step 1: Mix 3 mL of AA and 10 mL of deionized water to obtain a mixed solution;

[0062] Step 2:

[0063] First, 9.43 g (0.06 mol) of DMAEMA was added to 15 mL of acetone, and 3.48 g (0.03 mol) of maleate was added after mixing. Under nitrogen protection, the mixture was stirred at 50 ° C for 4 h. After the reaction was completed, it was cooled at low temperature, filtered under reduced pressure, and then vacuum dried at 65 ° C for 4 h to obtain white needle-shaped crystals of DMAEMA-MA.

[0064] Then, 3 mL of HEMA and 0.6 mL of BA were added to the mixed solution obtained in step 1, and after mixing, 0.1 g of DMAEMA-MA, 1 mL of ammonium persulfate aqueous solution (40 mg / mL) and 0.1 mL of TEMED were added, and the mixture was stirred to obtain a hydrogel precursor;

[0065] Step 3: The hydrogel precursor was ultrasonically defoamed for 10 minutes and then injected into the mold, and then reacted at 65°C for 4 hours, and then frozen at -20°C for 12 hours and thawed to room temperature to obtain a hydrogel.

[0066] Detection test

[0067] The mechanical properties of the hydrogel prepared in Example 3 are shown in the figure below: Figure 3 As shown in ad, Figure 3 As can be seen from a, it can easily lift a weight of 0.4kg. Figure 3b It can be seen that when the hydrogel was knotted and stretched to approximately ten times its original length, no rupture was observed. Figure 3 c It can be seen that the hydrogel is very strong and can resist external compression and recover immediately after the external force is removed. Figure 3 d It can be seen that the hydrogel is able to withstand the excision.

[0068] The swelling curves of the hydrogels prepared in Examples 2-3 and Comparative Examples are as follows: Figure 4 As shown, it can be seen that chitosan has successfully participated in the construction of the polymer network, giving the hydrogel anti-swelling properties.

[0069] The tensile stress-strain curves of the hydrogels prepared in Examples 1-3 are as follows: Figure 5 As shown, it can be seen that the tensile strength and elongation at break of the hydrogel prepared in Example 1 are 0.058 MPa and 1452%, respectively. The tensile strength and elongation at break of the hydrogel prepared in Example 2 are 0.195 MPa and 1022%, respectively. The tensile strength and elongation at break of the hydrogel prepared in Example 3 are 0.321 MPa and 1164%, respectively.

[0070] The stress-strain curves of the hydrogels obtained in Examples 1-3 after underwater immersion are shown in FIG. Figure 6-8 As shown, it can be seen that the stress, strain, elastic modulus and toughness of the hydrogels prepared in Examples 1-3 are increased as time goes by when they are immersed in water. The presence of butyl acrylate and 2-hydroxyethyl methacrylate in the system effectively enhances the binding force of the hydrogel in water. At the same time, the electrostatic interaction between DMAEMA-MA and chitosan keeps the hydrogel structure stable underwater and gives the hydrogel excellent mechanical properties. In addition, DMAEMA-MA further improves the stability of the hydrogel structure underwater by reducing the hydrophilic groups exposed in water.

[0071] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an anti-swelling hydrogel with excellent mechanical properties, characterized in that: The method proceeds as follows: Step 1: First, mix acrylic acid and deionized water, then add chitosan, heat and stir until completely dissolved to obtain a mixed solution; Step 2: Add 2-hydroxyethyl methacrylate and butyl acrylate to the mixed solution, mix well, add dimethylaminoethyl methacrylate maleate, ammonium persulfate aqueous solution and tetramethylethylenediamine, and stir to obtain a hydrogel prepolymer; Step 3: After degassing, the hydrogel precursor is injected into the mold, and then reacted at 60-70°C for 3-5 hours, and then frozen at -15 to -25°C for 10-14 hours, and thawed to room temperature to obtain an anti-swelling hydrogel with excellent mechanical properties.

2. The method according to claim 1, characterized in that: In step 1, the volume ratio of acrylic acid to deionized water is (2-4):10, and the mass ratio of chitosan to deionized water is (0.035-0.045):

1.

3. The method according to claim 1, characterized in that The volume ratio of 2-hydroxyethyl methacrylate and butyl acrylate in step 2 to the deionized water in step 1 is (2-4):(0.5-0.7):

10.

4. The method according to claim 1, characterized in that In step 2, dimethylaminoethyl methacrylate maleate is prepared according to the following steps: Add dimethylaminoethyl methacrylate to acetone, mix well and then add maleate. Under nitrogen protection, stir and react at 50°C for 4 hours. After the reaction is completed, cool at low temperature, filter under reduced pressure and dry in vacuum to obtain white needle-shaped crystals of dimethylaminoethyl methacrylate maleate.

5. The method according to claim 4, characterized in that The molar ratio of dimethylaminoethyl methacrylate to maleic acid salt is (1.8-2.2):

1.

6. The method according to claim 1, characterized in that The mass ratio of dimethylaminoethyl methacrylate maleate in step 2 to the deionized water in step 1 is (0.01-0.05):1, the volume ratio of the ammonium persulfate aqueous solution, tetramethylethylenediamine and the deionized water in step 1 is (0.8-1.2):(0.08-0.12):10, and the concentration of the ammonium persulfate aqueous solution is 35-45 mg / mL.

7. The method according to claim 1, characterized in that In step 3, the bubbles are removed by ultrasound, and the ultrasound time is 8-12 minutes.

8. The method according to claim 1, characterized in that In step 3, the reaction was carried out at 65°C for 4 h and frozen at -20°C for 12 h.

9. The anti-swelling hydrogel with excellent mechanical properties obtained by the method according to any one of claims 1 to 8, characterized in that: It has an interpenetrating double network, in which chitosan molecular chains serve as the first network, butyl acrylate, 2-hydroxyethyl methacrylate and acrylic acid are used as monomers, and dimethylaminoethyl methacrylate maleate is used as a crosslinking agent to form a second network. The first network and the second network form a double network physical crosslinking structure with hydrogen bonding.

10. The anti-swelling hydrogel with excellent mechanical properties obtained by the method according to any one of claims 1 to 8 is used to prepare flexible wearable electronic devices.

Citation Information

Patent Citations

  • Preparation method of high-strength hydrogel

    CN103739861A

  • Sodium alginate-acrylamide composite aquagel, and preparation method and application thereof

    CN105504166A